Profiling the growth conditions and persistent organic pollutants (POPS) tolerance of Phenoliferia glacialis USM-PSY62 - Ain Nur Afifah Azman; Shazilah Kamaruddin; Quay, Doris Huai Xia; Farah Diba Abu Bakar; Noor Haza Fazlin Hashim; Abdul Munir Abdul Murad; Izwan Bharudin (Penerbit Universiti Kebangsaan Malaysia, 2024)
Antarctica is characterized by extreme cold, isolated, and unique ecosystems. Nevertheless, Antarctica harbors diverse species of microorganisms, particularly in its ice-covered lakes and subglacial environments. These microorganisms have special adaptations to extreme cold and low-nutrient conditions. Some extremophiles, like psychrophiles can thrive in these harsh environments. Phenoliferia glacialis USM-PSY62, previously identified as Rhodotorula sp. USM-PSY62 is a psychrophilic yeast isolated from the ice brine of Antarctica. However, there is very little information on this psychrophilic yeast. This study aims to characterize the P. glacialis USM-PSY62 through the identification of the optimum growth parameters in different media (Yeast Peptone Dextrose, YPD & Yeast Malt, YM), temperature (4°C, 15°C, 20°C) and pH (6, 7, 8, 9) as well as their ability in carbon assimilation and extracellular enzyme production. It has an optimal growth in YPD compared to YM broth media. P. glacialis USM-PSY62 grows optimally at 15°C and pH 7.0. This Antarctic yeast enters the stationary phase on day six of incubation under optimum conditions. It appeared mainly as elongated-shape and oval-shaped with budding formation and was found to produce extracellular enzymes such as protease and amylase in the presence of 2% glucose concentration in YM media. P. glacialis USM-PSY62 also can assimilate various types of carbon sources including raffinose, arabinose, and maltose. Interestingly, the psychrophilic yeast presented growth in media supplemented with Persistent Organic Pollutants (POPs) such as dichlorophenyldichloroethylene (DDE) and polychlorinated biphenyl (PCB). These preliminary findings suggest that P. glacialis USM-PSY62 has tremendous potential for bioremediation application in polluted cold regions, as well as deepening our knowledge of its optimal growth conditions.